Nauczanie religii jako towarzyszenie: od powierzchowności do duchowości, do osobistego poznania Boga wcielonego - Osewska, Elżbieta (Studia Pastoralne, 2026)
According to the general understanding, accompanying involves first of all being in attendance, being with somebody, sharing the hardships of a journey, joys, but also difficulties, uncertainties, overcoming obstacles on the road together, defining the destination. If Religious Education wants to take on the function of accompanying children and the youth on the road to the contemporary Emmaus, then the fundamental condition is being in attendance and journey together. Therefore, the author of this article reflects upon the idea of the road to Emmaus and the role of school RE as accompanying youth leading from superficiality to spirituality to personal contact with God. Personal acquaintance with God incarnate assumes certain complementarity of God’s initiative and man’s action, cognition, conversion and trust. Thanks to His incarnation God has become audible and visible. Therefore, accompanying the pupil on the road to Emmaus should include both the verbal and visual processes starting from pupil’s inner chaos, his/her questions, problems, difficulties up to the spiritual sphere.